2008
DOI: 10.1590/s0034-89102008005000028
|View full text |Cite
|
Sign up to set email alerts
|

Uso de mamadeira no primeiro mês de vida: determinantes e influência na técnica de amamentação

Abstract: Uso de mamadeira no primeiro mês de vida: determinantes e infl uência na técnica de amamentaçãoBottle feeding during the fi rst month of life: determinants and effect on breastfeeding technique RESUMO OBJETIVO: Analisar a incidência e os determinantes do uso de mamadeira no primeiro mês de vida e possíveis efeitos dessa prática na técnica de amamentação. MÉTODOS:Estudo transversal aninhado em uma coorte contemporânea de Porto Alegre, RS, de junho a novembro de 2003. Durante um mês foram acompanhados 211 pares … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
31
0
21

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(57 citation statements)
references
References 8 publications
3
31
0
21
Order By: Relevance
“…shown that, at seven days of life, 21.3% of infants already use the bottle and at 30 days of life, this percentage increases to 46.9%, and the influence and support of maternal grandmother are usually related to the introduction of the feeding bottle [19]. The influence of maternal and paternal grandparents on bottle feeding for infants and consumption of water, teas and other types of milk has also been demonstrated in a recently published systematic review [21,22].…”
Section: Variablesmentioning
confidence: 86%
See 1 more Smart Citation
“…shown that, at seven days of life, 21.3% of infants already use the bottle and at 30 days of life, this percentage increases to 46.9%, and the influence and support of maternal grandmother are usually related to the introduction of the feeding bottle [19]. The influence of maternal and paternal grandparents on bottle feeding for infants and consumption of water, teas and other types of milk has also been demonstrated in a recently published systematic review [21,22].…”
Section: Variablesmentioning
confidence: 86%
“…The feeding bottle, in addition to negatively influencing the child's orofacial development, is associated with a greater chance of developing deleterious oral habits and malocclusions, also negatively influencing the EBF practice [19,20]. Still according to the authors, mothers with nipple traumas offer bottles to their children with the intention of spacing feedings, which can lead to lower milk production, increasing bottle use and replacing EBF.…”
Section: Variablesmentioning
confidence: 99%
“…Furthermore, the dynamism of these relations in time and space hinders or are an obstacle to building a single model capable of explaining the problem. 4,5,9,10,15,21,23 In the case of this study, out of the 14 variables distributed across the three levels of the explanatory model, ten were considered statistically signifi cant (p < 0.20), and were included in the multivariate analysis. Among the latter, factors which were initially considered important, such as income, occupation, number of people in the household and enrollment with the Family Health Program, were excluded.…”
Section: Discussionmentioning
confidence: 99%
“…1,2,4,5,10 The most recent data on breastfeeding in Brazil are from the Second Survey on Breastfeeding Prevalence In regard to the fi rst study carried out in 1991, a a representative sample was chosen taking into account the representation of a set of indicators totaling 11 interest factors, among which 'prevalence and duration of milk feeding'. This sample was made up of 935 children under age fi ve for the state of Pernambuco and other states in the Northeast.…”
mentioning
confidence: 99%
See 1 more Smart Citation